Cases in Leadership - W. Glenn Rowe (SAGE, 2013)
Cases in Leadership is a unique collection of 30 real-world leadership cases from Ivey Publishing plus fourteen practitioner readings from the Ivey Business Journal. This casebook helps business students gain a better understanding of leadership and enables them to be more effective leaders through their careers. The selected cases are about complex leadership issues that require the attention of the decision-maker in each case.